Control of Grid Connected PV Systems with an Emphasis on Maximum Power Extraction - Wali, Kartik; Chakrasali, R.L. (Journal of Power Electronics and Devices, 2023)
The demand for electricity from conventional power plants is increasing and global warming is increasing due to the emission of greenhouse gases into the environment. At present there is a move towards the use of renewable energy sources (RES) such as solar energy, wind energy, etc. Solar energy is the dominant source due to its abundant availability, pollution and reasonable cost. Solar energy satisfies the increasing demand for energy by integrating it with the existing conventional power plant grid. This paper proposes grid-connected PV system that converter solar energy to electrical energy. PV array is controlled and optimized by using a maximum power point tracking (MPPT) algorithm. Detailed analysis of the PV module connected to the grid is simulated with the help of MATLAB software and the results are analyzed.